Distributional disputes and civil conflict - Herschel I. Grossman (Brown University, Department of Economics, 2003)
Some polities are able to use constitutionally prescribed political processes to settle distributional disputes, whereas in other polities distributional disputes result in civil conflict. Theoretical analysis reveals that the following properties help to make it possible to design a self-enforcing constitution that can settle recurring distributional disputes between social classes without civil conflict: Neither social class has a big advantage in civil conflict. The expected incremental costs of civil conflict are large relative to aggregate appropriable economic rents. Both social classes are greatly concerned about the future consequences of their current actions. Theoretical analysis also reveals that a self-enforcing constitution can require limitations on the prerogatives of winners of constitutional contests such that on average the distribution of appropriable economic rents under the constitution is not too favorable to one social class or the other and such that the outcome of a constitutional contest does not matter too much for the current distribution of economic rents.
Keywords: D74; 330; Distributional Disputes; Social Classes; Self-Enforcing Constitution; Civil Conflict; Verteilungskonflikt; Bürgerkrieg; Public Choice; Theorie